Stereotypes in Female Leadership - Delgado Vázquez, María Soraya; Núñez Hernández, Luz María; Silva Acosta, Frida Camila (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2024)
This essay delves into the topic of stereotypes in female leadership, analyzing how these prejudices and limiting beliefs affect the participation and promotion of women in leadership roles. For this reason, stereotypes in female leadership are a relevant and complex topic that faces several challenges, which can be negatively associated with traits attributed to weakness.So, gender stereotypes are exposed as socially shared, rigid, and generator images that describe the traits that are affirmed that people from a certain social group are said to possess. This can result in a lack of confidence in women, and self-exclusion from positions of responsibility, making it difficult for women to ascend to senior positions. Likewise, the need for a cultural and organizational change that promotes diversity and gender equality in companies is raised.Finally, it is considered that to build more equitable and inclusive societies it is important to challenge these stereotypes, demonstrate that it is essential to change perceptions of what it means to be a leader, promote confidence in women, and break down the glass ceiling in organizations.
Keywords: Gender stereotypes; Female leadership; Glass ceiling.